ANALYSIS OF SOCIAL VALUES IN THE FILM “AIR MATA DI UJUNG SAJADAH”BY KEY MANGUNSONG: Analisis Nilai Sosial Dalam Film Air Mata di Ujung Sajadah Karya Key Mangunsong - Abdul Malik; Zaitun; Harry Andheska; Dodi Irawan; Fabio Testy Ariance Loren; Feby Nurumy (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Abstract This study aims to describe the social values contained in the film Air Mata di Ujung Sajadah by Key Mangunsong using a literary sociology approach. The research focuses on the depiction of social values based on their nature, characteristics, and levels of existence as reflected through the characters, dialogues, and storyline in the film. This is a qualitative descriptive study employing content analysis methods. The results of the analysis indicate that the film contains various social values, including: (1) personality values, encompassing egoism, ideas, and personal concepts; (2) biological values, such as emotional bonds and maternal instincts; (3) obedience values, in the form of respect, honesty, and responsibility; (4) material values, including heritage, education, and physical conditions; (5) knowledge values, involving sacrifice, perseverance, and honesty in action; and (6) togetherness values, such as cooperation, affection, emotional support, and shared struggle. These social values are powerfully conveyed through the characters’ inner conflicts, family struggles, and search for identity. The film not only entertains but also offers meaningful lessons about the importance of social bonds, religious values, and moral responsibility in life. Thus, Air Mata di Ujung Sajadah is a film worthy of being used as an educational medium rich in moral messages and character values.